Laser beam oscillation welding for fatigue properties enhancement of tailor-welded blanks - Šebestová, Hana; Jambor, Michal; Horník, Petr; Novotný, Jan; Mrňa, Libor (Thin-walled structures, 2024)
•Laser welding without beam oscillation resulted in welds with severe root defects.•Welding with circle and cardioid oscillation mode reduced the root defects, while the lean root was present in the welds made with linear oscillation.•Root defects did not negatively affect the tensile strength of a weld joint nor its deep-drawability.•Applying any beam oscillation mode significantly improved the joints' fatigue properties.•The oscillation mode influences the extent of phase transformation and, thereby, the level and distribution of residual stresses. The fatigue properties are influenced both by these factors as well as by the presence and geometry of weld notches. Dissimilar thickness laser welded tailored blanks of two low-alloyed carbon steel grades were fabricated. Laser welds made without beam oscillation exhibited serious root undercuts. Although these notches did not degrade the tensile strength, they were detrimental to the fatigue lifetime of a weld joint. Therefore, laser welds with three different beam oscillation modes to modify the root were examined. Application of beam oscillation improved fatigue properties in all tested cases. The best results were achieved with line oscillation, even though this mode did not suppress weld root notches, suggesting other factors, besides joint geometry, contributing to the resulting fatigue properties.